2021
DOI: 10.20517/2394-5079.2020.122
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration: metabolic and epigenetic regulation

Abstract: The liver is bestowed with an extraordinary regenerative capability, which is accomplished by a well-coordinated cellular and molecular response at different phases of regeneration. Metabolism, as the primary function of liver, displays various alterations as a consequence of hepatic insufficiency from an injury. These metabolic perturbations are physiologically relevant for promoting hepatocellular proliferation and regeneration. On the other hand, proliferation of otherwise quiescent hepatocytes and accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…It is also worth noting that previous studies have indirectly demonstrated that FAO effectively promotes the process of liver regeneration by reshaping the balance between the demand for and supply of fatty acids by inhibiting PTEN or providing ATP and carnitine (29)(30)(31). Suppressed transient lipid droplet accumulation after PHx resulted in impairment of liver regeneration, with biological implications linked to adiposederived hormones like adiponectin and leptin, or ATP production (32,33). A most recent publication also suggested that Acetyl-CoA provided by FAO can promote histone acetylation during liver regeneration, but the relevant research was conducted at least 2 days after PHx, which were not be able to provide 28 sufficient evidence in explaining the role of FAO in the initiation of liver regeneration (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that previous studies have indirectly demonstrated that FAO effectively promotes the process of liver regeneration by reshaping the balance between the demand for and supply of fatty acids by inhibiting PTEN or providing ATP and carnitine (29)(30)(31). Suppressed transient lipid droplet accumulation after PHx resulted in impairment of liver regeneration, with biological implications linked to adiposederived hormones like adiponectin and leptin, or ATP production (32,33). A most recent publication also suggested that Acetyl-CoA provided by FAO can promote histone acetylation during liver regeneration, but the relevant research was conducted at least 2 days after PHx, which were not be able to provide 28 sufficient evidence in explaining the role of FAO in the initiation of liver regeneration (34).…”
Section: Discussionmentioning
confidence: 99%
“…All data associated with this study are included within the main text or the Supplementary information. Raw RNA-seq data, Untargeted Metabolomics data, Spatial Metabolomics data, and CUT&Tag data generated in the present 33 study have been deposited at NCBI GEO databank and other public databases and will be publicly available as of the date of publication. Other data reported in this paper will be shared by the corresponding author upon request.…”
Section: Conflict Of Interestmentioning
confidence: 99%